ChemInform Abstract: AlCl3‐Mediated Hydroarylation—Heteroarylation in a Single Pot: A Direct Access to Densely Functionalized Olefins of Pharmacological Interest. Issue 43 (7th October 2013) - Nakhi, Ali; Archana, Sivakumar; Seerapu, Guru Pavan Kumar; Chennubhotla, Keerthana Sarma; Kumar, Kummari Lalith; Kulkarni, Pushkar; Haldar, Devyani; Pal, Manojit
Abstract With a view to find novel sirtuin inhibitors, a series of substituted quinoxalines (V) (30 examples) is prepared by a hydroarylation—heteroarylation reaction.